Effect of equine-derived Lactobacillus M11 on the reproductive performance of KM pregnant female mice - Liu, Yuanyi; Xu, Haoran; Cao, Jialong; He, Qianqian; Wang, Na; Du, Ming; Zhao, Yiping; Dugarjaviin, Manglai; Zhang, Xinzhuang (Frontiers in Microbiology, 2026)
IntroductionThis study aimed to evaluate the effects of equine-derived Lactobacillus M11 on reproductive performance and metabolic profiles in pregnant Kunming (KM) mice. The objective was to explore the potential of M11 as a safe and effective alternative to antibiotics in antibiotic-free farming systems.MethodsSpecific pathogen-free (SPF) female KM mice were randomly assigned to a blank control group (BC) and three intervention groups (M11-L, M11-M, M11-H). The intervention groups received daily gavage of M11 at low (1.0 × 107 CFU/mL), medium (1.0 × 108 CFU/mL), and high (1.0 × 109 CFU/mL) concentrations for 21 days. Host physiological parameters, metagenomic profiles, and metabolomic signatures were analyzed to assess the impact of M11 supplementation.Results(1) Host Physiology and Biochemistry: The M11-H group exhibited a significant elevation in albumin (ALB; 40.30 ± 1.75 g/L), suggesting enhanced nutritional status or hepatic protein synthesis. The M11-L group showed transient increases in alanine aminotransferase (ALT; 59.57 ± 10.34 U/L) and total cholesterol (TC; 2.90 ± 0.24 mmol/L), indicative of adaptive hepatic lipid metabolism. (2) Microbial Community Reconfiguration: Metagenomic analysis revealed significant structural shifts in the gut microbiota between the BC and M11-H groups. Notably, the M11-H group showed enrichment of Bacillota, which correlated with “O-antigen nucleotide sugar biosynthesis,” while differences in Pseudomonadota were associated with immune regulation. (3) Metabolomic Profiling: Partial Least Squares Discriminant Analysis (PLS-DA) demonstrated clear separation in the cecal metabolome space. KEGG pathway enrichment analysis highlighted significant alterations in “glycine/serine/threonine metabolism” and “arginine/proline metabolism” pathways. (4) Integrated Multi-Omics Analysis: Correlation analysis identified a significant positive association between s_Clostridiaceae_bacterium (Bacillota) and specific metabolites (3-hydroxy-4-aminopyridine sulfate), suggesting the formation of a regulatory “gut-reproductive axis.”DiscussionThe results demonstrate that Lactobacillus M11 improves metabolic support during pregnancy through three primary mechanisms: modulation of the gut microbiota, activation of key metabolic pathways, and enhancement of antioxidant capacity. These findings provide a theoretical basis for the application of probiotic-mediated reproductive support in antibiotic-free farming, highlighting M11 as a promising candidate for improving livestock health and productivity.